Penggunaan Media Gambar dalam Meningkatkan Hasil Belajar Ipa Siswa Kelas Vii Upt Smp Negeri 3 Anggeraja Kabupaten Enrekang - Jumiati Jumiati (CV. Syntax Corporation Indonesia, 2023)
The formulation of this research problem is whether the use of image media can improve the learning outcomes of grade VII students in science subjects UPT SMP Negeri 3 Anggeraja, Enrekang Regency. This goal is to find out whether the use of image media can improve the learning achievement of science class VII circulatory device material in humans. This type of research is Classroom action reasearch. The subject of this study was class VII UPT SMP Negeri 3 Anggeraja Enrekang Regency which amounted to 26 students. Data collection techniques in this study are by observation, written tests. From the results of the study, it can be concluded that using Image media can improve the learning outcomes of grade VII students in the science subjects of UPT SMP Negeri 3 Anggeraja. This can be seen from the improvement in each cycle. Where in the initial ability (pretest) obtained learning results with an average of 55 and a percentage of completeness of 42%, for that the researchers carried out cycle I, the results obtained with an average value of 64 and a percentage of completeness of 57%, then carried out cycle II increased with an average value of 75 and learning completeness of 88%.